PENGARUH BUDAYA DAN SOSIAL TERHADAP KEPUTUSAN ANGGOTA DALAM MEMILIH PRODUK PEMBIAYAAN RAHN DI BMT UGT SIDOGIRI CAPEM SRONO KABUPATEN BANYUWANGI - Inayah, Nurul; Fitroh, Adini Anwaril (Jurnal Ekonomi Syariah Darussalam, 2021)
The purpose of this study is to find out and analyze cultural (X1) and social (X2) variables simultaneously have a significant effect on the decision of members (Y) in choosing rahn financing products at BMG UGT Sidogiri Capem Srono Banyuwangi Regency. Research Results simultaneously cultural (X1) and social (X2) influence the decision of members (Y) in choosing rahn financing products at BMG UGT Sidogiri Capem Srono Banyuwangi Regency. Research conclusions 1) the members' decision in choosing a rahn financing product is based on culture. It also means that all values, habits, perceptions, preferences, and behaviors that develop in society influence members in choosing rahn financing products in other words cultural, subcultural and social class elements are the basis for members in choosing rahn financing products. 2) Member of BMT UGT Sidogiri Capem Srono Banyuwangi Regency decided to take financing because it is based on meeting family needs. 3) The decision to take financing is influenced by cultural variables, and social variables. In terms of cultural variables, the stronger the culture, then someone is encouraged to take funding. Regarding social variables, if someone has a good social interaction, then encourage to decide to take financing.